Best Vitelliform Macular Dystrophy (BVMD) is a phenocopy of North Carolina Macular Dystrophy (NCMD/MCDR1). (4th May 2022) - Small, Kent W.; Jampol, Lee M.; Bakall, Benjamin; Small, Leslie; Wiggins, Robert; Agemy, Steven; Udar, Nitin; Avetisjan, Jessica; Vincent, Andrea; Shaya, Fadi S.
ABSTRACT: Purpose: North Carolina Macular Dystrophy (NCMD) and Best Vitelliform Macular Dystrophy (BVMD) are rare autosomal dominant macular dystrophies. Both BVMD and NCMD have markedly variable expressivity. In some individuals, it can be difficult to differentiate between the two disease entities. Methods: Clinical findings including fundus photography, fundus autofluorescence (FAF), and spectral domain optical coherence tomography (SD-OCT) were evaluated in 5 individuals with NCMD and 3 with BMD. Electrooculography (EOG) was performed in 2 NCMD subjects. Molecular diagnosis was performed using Sanger DNA sequencing. IRB approval was obtained. Results: Five NCMD subjects had clinical findings indistinguishable from three of our BVMD subjects. Molecular diagnosis was confirmed in all but one BVMD subject who had an abnormal EOG prior to discovery of the BEST1 gene. Two NCMD subjects had an abnormal EOG with a normal ERG, which has been considered a unique feature of BVMD. SD-OCT in one BVMD subject demonstrated a small lucency/excavation into the choroid similar to that in grade 3 lesions of NCMD. Two NCMD subjects had elevated sub-macular lesions giving a pseudo-vitelliform appearance on OCT similar to BVMD. Conclusion: Best Vitelliform Macular Dystrophy can be a phenocopy of NCMD. There is considerable clinical overlap between NCMD and BVMD, which can cause diagnostic inaccuracies. Our new findings demonstrate that like BVMD, NCMD can also have an abnormal EOG with a normal ERG. The overlapping phenotypes of BVMD with NCMD may provide insights into the mechanisms of the macular changes.